PENDIRIAN POJOK LITERASI DI SD NEGERI NEGLASARI UNTUK MENUMBUHKAN MINAT BACA SISWA - Muhamad Rifda Firdaus. S (LPPM Universitas Nusa Putra, 2024)
Abstract The creation of a literacy corner at Neglasari State Elementary School in Cikakak Village aims to increase students' interest in reading, considering the still minimal use of school libraries. Before the corner was created, activities such as writing and reading assignments were carried out to foster students' interest in reading. This community service program includes cleaning and painting the school corridors and making shelves from used plastic cupboards. The books placed in the literacy corner come from the school library. The challenges faced include limited shelf capacity so that the number of books that can be displayed is limited. The results show that students are enthusiastic about using the literacy corner and their interest in reading is starting to grow. In conclusion, this literacy corner has been able to facilitate access to books and create a conducive environment for literacy activities at school, although there is still a need for improvement in terms of storage capacity. Keywords: Literacy corner, reading interest, education, Neglasari State Elementary School Abstrak Dibuatnya pojok literasi di SD Negeri Neglasari Desa Cikakak bertujuan untuk meningkatkan minat membaca siswa, mengingat masih sedikitnya pemanfaatan perpustakaan sekolah. Sebelum dibuat pojok, dilakukan kegiatan seperti tugas menulis dan membaca untuk menumbuhkan minat membaca siswa. Program pengabdian ini meliputi pembersihan dan pengecatan koridor sekolah serta pembuatan rak dari lemari plastik bekas. Buku-buku yang ditempatkan di pojok literasi berasal dari perpustakaan sekolah. Tantangan yang dihadapi antara lain terbatasnya kapasitas rak sehingga jumlah buku yang dapat dipajang terbatas. Hasilnya menunjukkan bahwa siswa antusias menggunakan pojok literasi dan minat membaca mulai tumbuh. Kesimpulannya, sudut literasi ini telah mampu mempermudah akses terhadap buku dan menciptakan lingkungan yang kondusif bagi kegiatan literasi di sekolah, meskipun masih perlu peningkatan dalam hal kemampuan penyimpanan. Kata kunci: Pojok literasi, minat baca, pendidikan, SD Negeri Neglasari